Pole piece structure, secondary battery and electric device
By incorporating LiMnaFebPO4 into the ternary positive electrode material, the problem of lithium-ion lithium-ion battery with negative electrode during charging is solved, and the battery cycle performance is improved and the service life is extended.
Patent Information
- Application Number
- CN202411241876.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-11
- Publication Date
- 2025-01-17
AI Technical Summary
During the charging process of the existing ternary positive electrode lithium-ion batteries, the negative electrode sheet will cause lithium extraction, affecting the service life.
By incorporating LiMnaFebPO4 into the ternary positive electrode material, the lithium ions in LiMnaFebPO4 are released during the charging process, and the crystal lattice shrinks, which increases the gaps of the positive electrode sheet, and stores the electrolyte extruded due to the expansion of the negative electrode sheet. Lithium ions are re-embedded to avoid lithium evolution caused by untimely reflux of the electrolyte.
It effectively avoids the occurrence of lithium precipitation in the negative electrode, improves the cycle performance of the battery, and extends the service life of the battery.
Smart Images

Figure CN119324200A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and specifically to a pole piece structure, a secondary battery, and an electrical device Background Art
[0002] Lithium-ion batteries have become the most popular energy storage systems due to their low cost, long life, good safety, etc., and are now widely used in fields such as pure electric vehicles, hybrid electric vehicles, and smart grids. Among them, ternary cathode lithium-ion batteries are particularly widely used. However, during the charging process of existing ternary cathode lithium-ion batteries, lithium deposition will occur on the negative electrode pole piece, affecting the service life.
[0003] Therefore, it is necessary to develop a pole piece structure that can avoid lithium deposition on the negative electrode, improve the cycle performance of ternary cathode lithium-ion batteries, and extend the service life of the batteries. Summary of the Invention
[0004] In view of the problems in the background art, the present application provides a pole piece structure that can avoid lithium deposition on the negative electrode, improve the battery cycle performance, and extend the service life of the battery.
[0005] The pole piece structure provided in the first aspect of the present application includes a positive electrode pole piece and a negative electrode pole piece. The positive electrode pole piece includes a positive electrode active material. The positive electrode active material includes a ternary positive electrode material and a mixture of LiMn a Fe b PO4, where 0 ≤ a < 1, 0 < b ≤ 1, and a + b = 1. The negative electrode pole piece includes a negative electrode active material. The negative electrode active material includes at least one of a carbon-based material and a silicon-based material.
[0006] During the charging process, the negative electrode pole piece expands and the porosity decreases, and the electrolyte will be extruded from the negative electrode. In the present application, by doping LiMn a Fe b PO4 into the ternary positive electrode material, during the charging process, lithium ions in LiMn a Fe b PO4 are removed, and the degree of lattice contraction is high, resulting in an increase in the voids of the positive electrode pole piece. Therefore, the electrolyte extruded due to the expansion of the negative electrode pole piece can be stored. During discharge, lithium ions re-embed into the lattice, extruding the electrolyte, enabling it to flow back to the negative electrode in time, thereby avoiding lithium deposition on the negative electrode caused by untimely electrolyte reflux during the next charge. When this pole piece structure is used in a secondary battery, it can improve the cycle performance of the battery and extend the service life of the battery.
[0007] In some embodiments, according to the first aspect, a first example of the first aspect is proposed, where the negative electrode active material includes a carbon-based material and a silicon-based material.
[0008] Silicon-based materials have attracted widespread attention due to their high capacity, but they have a serious volume effect, which will produce a large volume expansion during charging, causing the electrolyte to be squeezed out of the negative electrode. This application not only improves the battery capacity by mixing carbon-based materials and silicon-based materials and matching them with the positive electrode sheet described above, but also avoids the lithium precipitation phenomenon caused by the electrolyte being squeezed out and unable to flow back to the negative electrode in time.
[0009] In some embodiments, LiMn a Fe b The mass ratio of PO4 to the ternary positive electrode material is 0.01-0.7.
[0010] In some embodiments, the mass ratio of the silicon-based material to the carbon-based material is 0.01-0.1.
[0011] In some embodiments, the mass ratio of the silicon-based material to the carbon-based material is defined as P, and LiMn is defined as a Fe b The mass ratio of PO4 to the ternary positive electrode material is Q, then R=Q / P satisfies: 0.5≤R≤15.
[0012] LiMn a Fe b The mass ratio of PO4 to ternary cathode materials is closely related to the mass ratio of silicon-based materials to carbon-based materials. The higher the content of silicon-based materials, the more obvious the expansion of the negative electrode, and the more LiMn required for the positive electrode. a Fe b The more PO4, the more LiMn a Fe b Too high PO4 content will lead to deterioration of the cycle because LiMn a Fe b PO4 decays rapidly under the ternary system voltage. Therefore, LiMn a Fe b The proportion of PO4 should match the proportion of silicon-based materials in the negative electrode and should not be too high.
[0013] In some embodiments, according to the first aspect, a third example of the first aspect is proposed, Q=(1-70):100.
[0014] By optimizing LiMn a Fe b The mass ratio of PO4 to ternary positive electrode material is beneficial to improving the battery's cycle performance and extending the battery's service life.
[0015] In some embodiments, according to the first aspect, a fourth example of the first aspect is proposed, where P=(1-10):100.
[0016] By optimizing the mass ratio of silicon-based materials to carbon-based materials, it is beneficial to improve the battery capacity and control the negative electrode expansion within an acceptable range.
[0017] In some embodiments, according to the first aspect, a fifth example of the first aspect is provided, wherein the positive electrode plate further includes a gas generating additive.
[0018] By adding gas-generating additives to the positive electrode, the porosity of the positive electrode sheet of the battery at full SOC can be further increased, the electrolyte storage capacity can be increased, and the cycle performance can be improved.
[0019] In some embodiments, according to the first aspect, a sixth example of the first aspect is provided, wherein the gas generating additive includes one or both of a non-lithium-supplementing gas generating additive and a lithium-supplementing gas generating additive.
[0020] The non-lithium-supplementing gas generating additive includes one or more of ammonium bicarbonate, sodium bicarbonate, and ammonium carbonate. The lithium-supplementing gas generating additive includes one or more of lithium nitride, lithium oxide, lithium peroxide, lithium squarate, and lithium oxalate.
[0021] By optimizing the types of gas-generating additives, it is helpful to increase the porosity of the positive electrode sheet.
[0022] In some embodiments, the mass ratio of the gas generating additive to the ternary cathode material is 0.001-0.1.
[0023] In some embodiments, the mass ratio of the gas generating additive to the ternary positive electrode material is 0.001-0.1, and the mass ratio of the silicon-based material to the carbon-based material is 0.01-0.1.
[0024] In some embodiments, according to the first aspect, a seventh example of the first aspect is proposed, the mass ratio of silicon-based material to carbon-based material is P, and the mass ratio of gas generating additive to ternary positive electrode material is defined as V, then W=V / P satisfies: 0.1≤W≤2.
[0025] The mass ratio of gas generating additives to ternary cathode materials is closely related to the mass ratio of silicon-based materials to carbon-based materials. As the amount of gas generating additives added increases, the porosity of the cathode plate increases, the amount of electrolyte that can be accommodated increases accordingly, and the cycle performance is improved. However, when the amount of gas generating additives is excessive, the porosity will be too high, which will cause the electrolyte demand to exceed the actual amount, and the cycle performance will deteriorate.
[0026] In some embodiments, according to the first aspect, an eighth example of the first aspect is proposed, V=(0.1-10):100.
[0027] Optimizing the mass ratio of gas-generating additives to ternary cathode materials can help improve the battery's cycle performance.
[0028] In some embodiments, according to the first aspect, a ninth example of the first aspect is provided, wherein the porosity of the positive electrode sheet is 15%-30%.
[0029] Optimizing the porosity of the positive electrode sheet can help improve the battery's cycle performance.
[0030] In some embodiments, according to the first aspect, a tenth example of the first aspect is provided, wherein the porosity of the negative electrode sheet is 20%-40%.
[0031] Optimizing the porosity of the negative electrode sheet can help improve the battery's cycle performance.
[0032] In some embodiments, according to the first aspect, an eleventh example of the first aspect is provided, wherein the ternary positive electrode material includes LiNi x Co y Mn z O2, where 0 <x<1,0<y<1,0<z<1,x+y+z=1。
[0033] By optimizing the types of ternary positive electrode materials, it is beneficial to increase battery energy density, improve battery cycle performance and extend battery life.
[0034] The second aspect of the present application provides a secondary battery, comprising the pole piece structure described in the first aspect of the present application.
[0035] In the technical solution of the embodiment of the present application, since the pole piece structure of the first aspect of the present application is adopted, the secondary battery of the present application has improved cycle performance and extended service life.
[0036] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a charge and discharge cycle curve diagram of the battery cells corresponding to Examples 1, 3 and 8 of the present application and Comparative Example 1.
[0038] Figure 2 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0039] Figure 3 yes Figure 2 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0040] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0041] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0042] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0043] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0044] Description of reference numerals:
[0045] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0046] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application is described in detail below in conjunction with specific embodiments. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.
[0047] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0048] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number itself, and the "multiple" in "one or more" means more than two (including two).
[0049] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0050] Lithium-ion batteries have become the most popular energy storage systems due to their low cost, long lifespan, and good safety performance. They are now widely used in pure electric vehicles, hybrid electric vehicles, smart grids, and other fields. Among them, ternary cathode lithium-ion batteries are particularly widely used. However, during the charging process of existing ternary cathode lithium-ion batteries, lithium plating occurs on the negative electrode sheet, which affects the service life. Therefore, it is necessary to develop a structure of the electrode sheet that can avoid lithium plating on the negative electrode, improve the cycling performance of ternary cathode lithium-ion batteries, and extend the service life.
[0051] Research has found that during the charging process, the negative electrode sheet, especially the negative electrode sheet containing silicon-based materials, will expand, resulting in a decrease in porosity, causing the electrolyte to be extruded from the negative electrode. During the discharging process, since the electrolyte cannot flow back to the negative electrode sheet in time, lithium plating occurs, affecting the service life of the battery.
[0052] This application proposes a structure of the electrode sheet with a positive-negative electrode matching. By doping LiMn a Fe b PO4 into the ternary cathode material, during the charging process, lithium ions in LiMn a Fe b PO4 are removed, and the degree of lattice contraction is high, resulting in an increase in voids in the positive electrode sheet. Therefore, the electrolyte extruded due to the expansion of the negative electrode sheet can be stored. During discharging, lithium ions re-embed into the lattice, extruding the electrolyte so that it can flow back to the negative electrode in time, thereby avoiding lithium plating on the negative electrode caused by the untimely flow-back of the electrolyte during the next charging. Therefore, the structure of the electrode sheet in this application successfully avoids the occurrence of lithium plating on the negative electrode. When this structure of the electrode sheet is used in secondary batteries, it can improve the cycling performance of the battery and extend the service life of the battery.
[0053] The technical solutions described in the embodiments of this application are not only applicable to the structure of the electrode sheet, but also applicable to secondary batteries using the structure of the electrode sheet and electrical devices using secondary batteries.
[0054] Specifically, in the first aspect of this application, a structure of the electrode sheet is provided, including a positive electrode sheet and a negative electrode sheet. The positive electrode sheet includes positive electrode active materials. The positive electrode active materials include a mixture of ternary cathode materials and LiMn a Fe b PO4, where 0 ≤ a < 1, 0 < b ≤ 1, and a + b = 1. The negative electrode sheet includes negative electrode active materials. The negative electrode active materials include at least one of carbon-based materials and silicon-based materials.
[0055] Compared with ternary cathode materials, LiMn a Fe b PO4 has a high lattice contraction during the charging process, which can increase the voids in the negative electrode sheet, and these voids can store the electrolyte extruded from the negative electrode. In some specific embodiments, LiMn a Feb PO4 can be lithium iron phosphate, lithium iron manganese phosphate or a mixture thereof.
[0056] In some specific embodiments, a can be 0, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85 or 0.9. b can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 1. Both a and b can be within the numerical range formed by any two of the above listed values as end values.
[0057] In some embodiments, according to the first aspect, a first example of the first aspect is provided, and the negative electrode active material includes a carbon-based material and a silicon-based material.
[0058] Silicon-based materials have attracted widespread attention due to their high capacity, but they have a serious volume effect, which will produce a large volume expansion during charging, causing the electrolyte to be squeezed out of the negative electrode. This application not only improves the battery capacity by mixing carbon-based materials and silicon-based materials and matching them with the positive electrode sheet described above, but also avoids the lithium precipitation phenomenon caused by the electrolyte being squeezed out and unable to flow back to the negative electrode in time.
[0059] In some embodiments, according to the first aspect, a second example of the first aspect is proposed, wherein the mass ratio of the silicon-based material to the carbon-based material is defined as P, and LiMn is defined as a Fe b The mass ratio of PO4 to the ternary positive electrode material is Q, then R=Q / P satisfies: 0.5≤R≤15.
[0060] LiMn a Fe b The mass ratio of PO4 to ternary cathode materials is closely related to the mass ratio of silicon-based materials to carbon-based materials. The higher the content of silicon-based materials, the more obvious the expansion of the negative electrode, and the more LiMn required for the positive electrode. a Fe b The more PO4, the more LiMn a Fe b Too high PO4 content will lead to deterioration of the cycle because LiMn a Fe b PO4 decays rapidly under the ternary system voltage. Therefore, LiMn a Fe b The proportion of PO4 should match the proportion of silicon-based materials in the negative electrode and should not be too high.
[0061] In some specific embodiments, R may be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, or 15. Alternatively, R may be 1-12, 3-10, or 5-8.
[0062] In some embodiments, according to the first aspect, a third example of the first aspect is proposed, Q=(1-70):100.
[0063] By optimizing LiMn a Fe b The mass ratio of PO4 to ternary positive electrode material is beneficial to improving the battery's cycle performance and extending the battery's service life.
[0064] In some specific embodiments, Q may be 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, 50:100, 55:100, 60:100, 65:100 or 70:100. Alternatively, Q may be 5:100 to 65:100.
[0065] In some embodiments, according to the first aspect, a fourth example of the first aspect is proposed, where P=(1-10):100.
[0066] By optimizing the mass ratio of silicon-based materials to carbon-based materials, it is beneficial to improve the battery capacity and control the negative electrode expansion within an acceptable range.
[0067] In some specific embodiments, P may be 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, 5:100, 5.5:100, 6:100, 6.5:100, 7:100, 7.5:100, 8:100, 8.5:100, 9:100, 9.5:100, or 10:100. Alternatively, P may be 1:100 to 5:100, 5:100 to 10:100, or 3:100 to 7:100.
[0068] In some embodiments, according to the first aspect, a fifth example of the first aspect is provided, wherein the positive electrode plate further includes a gas generating additive.
[0069] In this application, "gas generating additive" refers to a compound that can volatilize or decompose during the electrode preparation or charging process. As the gas generating additive volatilizes or decomposes, the porosity of the positive electrode increases, thereby increasing the electrolyte storage capacity.
[0070] By adding gas-generating additives to the positive electrode, the porosity of the positive electrode sheet of the battery at full SOC can be further increased, the electrolyte storage capacity can be increased, and the cycle performance can be improved.
[0071] In some embodiments, according to the first aspect, a sixth example of the first aspect is proposed, wherein the gas generating additive includes one or both of a non-lithium-supplementing gas generating additive and a lithium-supplementing gas generating additive. The non-lithium-supplementing gas generating additive includes one or more of ammonium bicarbonate, sodium bicarbonate, and ammonium carbonate. The lithium-supplementing gas generating additive includes one or more of lithium nitride, lithium oxide, lithium peroxide, lithium quarate Li2C4O4, and lithium oxalate.
[0072] By optimizing the types of gas-generating additives, it is helpful to increase the porosity of the positive electrode sheet.
[0073] The gas generating additive is a lithium replenishing type gas generating additive. The advantage of using a lithium replenishing type gas generating additive is that it can both increase the porosity of the positive electrode sheet and replenish lithium to the positive electrode sheet.
[0074] In some embodiments, according to the first aspect, a seventh example of the first aspect is proposed, the mass ratio of silicon-based material to carbon-based material is P, and the mass ratio of gas generating additive to ternary positive electrode material is defined as V, then W=V / P satisfies: 0.1≤W≤2.
[0075] The mass ratio of gas generating additives to ternary positive electrode materials is closely related to the mass ratio of silicon-based materials to carbon-based materials. As the amount of gas generating additives added increases, the porosity of the positive electrode sheet increases, the amount of electrolyte that can be accommodated increases accordingly, and the cycle performance is improved. However, when the amount of gas generating additives is excessive, the porosity will be too high, which will cause the electrolyte demand to exceed the actual amount and the cycle performance will deteriorate. In addition, too high a porosity will also reduce the battery energy density and waste effective space.
[0076] In some specific embodiments, W may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2. Alternatively, W may be 0.1-1.6, 0.3-1.5, or 0.5-1.
[0077] In some embodiments, according to the first aspect, an eighth example of the first aspect is provided, V=(0.1-10): 100. By optimizing the mass ratio of the gas generating additive to the ternary positive electrode material, the cycle performance of the battery is improved.
[0078] In some specific embodiments, V may be 0.1:100, 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, 5:100, 5.5:100, 6:100, 6.5:100, 7:100, 7.5:100, 8:100, 8.5:100, 9:100, 9.5:100, or 10:100. Alternatively, V may be 0.5:100 to 9:100 or 0.5:100 to 8:100.
[0079] In some embodiments, according to the first aspect, a ninth example of the first aspect is provided, wherein the porosity of the positive electrode sheet is 15%-30%.
[0080] The porosity of the electrode sheet refers to the percentage of the volume of the internal pores of the electrode sheet after rolling to the total volume of the electrode sheet after rolling. If the porosity of the electrode sheet is too low, the electrolyte will reduce the infiltration rate of the electrode sheet, affecting the performance of the battery. If the porosity is too high, the battery energy density will be reduced and the effective space will be wasted. By optimizing the porosity of the positive electrode sheet, it is beneficial to improve the cycle performance of the battery.
[0081] In addition to increasing the porosity of the positive electrode sheet by using a gas generating additive in the positive electrode slurry, other conventional physical pore-making methods may also be used, such as laser drilling or roller pressing (the roller has needle-like protrusions), etc. The present application does not specifically limit the pore-making method, as long as the porosity of the positive electrode sheet can be within the range of 15%-30%.
[0082] In some specific embodiments, the porosity of the positive electrode sheet may be 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5% or 30%. Optionally, the porosity of the positive electrode sheet may be 15%-28% or 19%-28%.
[0083] In some embodiments, according to the first aspect, a tenth example of the first aspect is provided, wherein the porosity of the negative electrode sheet is 20%-40%.
[0084] Optimizing the porosity of the negative electrode sheet can help improve the battery's cycle performance.
[0085] In some specific embodiments, the porosity of the negative electrode sheet may be 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5% or 40%. Optionally, the porosity of the negative electrode sheet may be 20%-30%.
[0086] In some embodiments, according to the first aspect, an eleventh example of the first aspect is provided, wherein the ternary positive electrode material includes LiNi x Co y Mn z O2, where 0 <x<1,0<y<1,0<z<1,x+y+z=1。
[0087] By optimizing the types of ternary positive electrode materials, it is beneficial to increase battery energy density, improve battery cycle performance and extend battery life.
[0088] The present application does not specifically limit the specific types of ternary positive electrode materials, and all commonly used ternary positive electrode materials in the art are applicable to the present application. In some specific embodiments, 0.3≤x≤0.95, 0.01≤y≤0.3, and 0.02≤z≤0.4.
[0089] For example, in some specific embodiments, the ternary cathode material includes LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) or more.
[0090] In some embodiments, according to the first aspect, a twelfth example of the first aspect is proposed, the carbon-based material includes one or more of artificial graphite, natural graphite, soft carbon, and hard carbon. Of course, the carbon-based material can also be other carbon-based materials commonly used in the art, which are not particularly limited here.
[0091] In some embodiments, according to the first aspect, a thirteenth example of the first aspect is proposed, and the silicon-based material includes one or more of elemental silicon, silicon oxide (such as silicon monoxide), silicon-carbon composites, silicon-nitrogen composites, silicon alloys, and pre-lithiation silicon-oxygen compounds.
[0092] In some embodiments, the silicon-based material is nano-sized.
[0093] The second aspect of the present application provides a secondary battery, comprising the pole piece structure described in the first aspect of the present application. Due to the adoption of the pole piece structure of the first aspect of the present application, the secondary battery of the present application has improved cycle performance and extended service life.
[0094] Generally, a secondary battery may include a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0095] [Negative electrode]
[0096] The negative electrode sheet generally includes a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector. The negative electrode film layer includes the negative electrode active material provided above in the present application.
[0097] The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil. The negative electrode film layer may also optionally include a binder, a conductive agent, and other optional additives.
[0098] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, conductive carbon black (Super P), graphene, and carbon nanofibers.
[0099] As an example, the binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0100] As an example, other optional auxiliary agents may be thickeners and dispersants (such as sodium carboxymethyl cellulose CMC-Na), PTC thermistor materials, etc.
[0101] [Positive electrode]
[0102] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector. The positive electrode film layer includes the positive electrode active material provided above in the present application.
[0103] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may be an aluminum foil. The positive electrode film layer may also optionally include a binder, a conductive agent, and other optional additives.
[0104] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, conductive carbon black (Super P), graphene, and carbon nanofibers.
[0105] As an example, the binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0106] [Isolation film]
[0107] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0108] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0109] [Electrolyte]
[0110] The electrolyte plays a role of conducting ions between the positive electrode and the negative electrode. The electrolyte may include an electrolyte salt and a solvent.
[0111] As an example, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0112] As an example, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0113] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0114] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0115] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0116] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0117] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 2 The battery cell 5 is a square structure as an example.
[0118] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0119] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0120] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0121] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0122] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0123] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0124] In addition, the present application also provides an electric device, the electric device includes the secondary battery provided in the present application, and the secondary battery includes at least one of a battery cell, a battery module and a battery pack. The secondary battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0125] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements. Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of the power source, a battery pack or a battery module can be used.
[0126] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0127] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.
[0128] Example
[0129] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present application.
[0130] The materials used in the examples of this application can all be obtained commercially.
[0131] Preparation of lithium-ion batteries
[0132] Example 1
[0133] Preparation of positive electrode: Lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25PO4, conductive carbon black (Super-P), polyvinylidene fluoride (PVDF) are mixed with N,N-dimethylpyrrolidone (NMP) at a weight ratio of 90:4.5:3:1.5, stirred evenly to obtain a slurry for coating the positive electrode, and the slurry is evenly coated on both sides of the aluminum foil. The electrode is cold pressed and sliced (i.e., the electrode is cut and cut into the required size) to obtain the positive electrode.
[0134] Preparation of negative electrode sheet: artificial graphite, nano silicon, conductive carbon black (Super-P), carbon nanotubes, sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR) are mixed with deionized water at a weight ratio of 100:5:0.5:0.1:1:1.5, and stirred evenly to obtain a slurry for coating the negative electrode sheet. The viscosity can be adjusted by deionized water during the stirring process. Then, the slurry is coated on both sides of a 6μm thick copper foil with a certain width. The capacity per unit area of both sides is the same, and the negative electrode sheet is obtained by cold pressing and slicing.
[0135] Preparation of lithium-ion battery: The positive electrode sheet, separator and negative electrode sheet are wound into a battery cell, and the lithium-ion battery is made through the welding of the tabs, packaging with aluminum shell, liquid injection, packaging formation and vacuum molding. The battery cell is 148mm wide, 28mm thick, 98mm high and has a capacity of 60Ah. Among them, the electrolyte is a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) containing LiPF6 at a concentration of 1M (the volume ratio of EC and DMCDE is 1:2). A 7μm thick PE separator is used.
[0136] Example 2
[0137] The method is the same as that in Example 1, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 78.75:15.75:3:1.5.
[0138] Example 3
[0139] The method is the same as that in Example 1, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 70:24.5:3:1.5.
[0140] Example 4
[0141] The method is the same as that in Example 1, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 59:35.5:3:1.5.
[0142] Example 5
[0143] The method is the same as that of Example 3, except that lithium squarate is added as a gas-generating additive, wherein lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O 2) 、LiMn 0.75 Fe 0.25 The weight ratio of PO4, lithium squarate, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is 70:24.5:0.35:3:1.5.
[0144] Example 6
[0145] The method is the same as that in Example 5, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, lithium squarate, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 70:24.5:0.7:3:1.5.
[0146] Example 7
[0147] The method is the same as that in Example 5, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, lithium squarate, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 70:24.5:1.4:3:1.5.
[0148] Example 8
[0149] The method is the same as that in Example 5, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, lithium squarate, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 70:24.5:2.1:3:1.5.
[0150] Example 9
[0151] The method is the same as that in Example 5, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, lithium squarate, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 70:24.5:4.2:3:1.5.
[0152] Example 10
[0153] The method is the same as that in Example 5, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, lithium squarate, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 70:24.5:5.6:3:1.5.
[0154] Embodiment 11
[0155] The method is the same as that of Example 5, except that LiMn 0.75 Fe 0.25 PO4 replaced by LiMn 0.1 Fe 0.9 PO4.
[0156] Example 12
[0157] The method is the same as that of Example 5, except that LiMn 0.75 Fe 0.25 PO4 replaced by LiMn 0.3 Fe 0.7 PO4.
[0158] Embodiment 13
[0159] The method is the same as that of Example 5, except that LiMn 0.75 Fe 0.25 PO4 replaced by LiMn 0.5 Fe 0.5 PO4.
[0160] Embodiment 14
[0161] The method is the same as that of Example 5, except that LiMn 0.75 Fe 0.25 PO4 replaced by LiMn 0.9 Fe 0.1 PO4.
[0162] Embodiment 15
[0163] The method is the same as that of Example 5, except that LiMn 0.75 Fe 0.25 PO4 is replaced by LiFePO4.
[0164] Example 16
[0165] The method is the same as that of Example 5, except that no nano-silicon is added to the negative electrode plate.
[0166] Embodiment 17
[0167] The method is the same as that in Example 5, except that lithium nitride is replaced by lithium nitride.
[0168] Embodiment 18
[0169] The method is the same as that in Example 5, except that lithium squarate is replaced by lithium oxide.
[0170] Embodiment 19
[0171] The method is the same as that in Example 5, except that lithium squarate is replaced by lithium peroxide.
[0172] Embodiment 20
[0173] The method is the same as that in Example 5, except that lithium squarate is replaced by lithium peroxalate.
[0174] Embodiment 21
[0175] The method is the same as that of Example 5, except that lithium squarate is replaced by ammonium percarbonate.
[0176] Embodiment 22
[0177] The method is the same as that in Example 5, except that lithium squarate is replaced by sodium percarbonate.
[0178] Embodiment 23
[0179] The method is the same as that in Example 5, except that LiNi 0.6 Co 0.2 Mn 0.2 O2 is replaced by
[0180] LiNi 0.5 Co 0.2 Mn 0.3 O2.
[0181] Embodiment 24
[0182] The method is the same as that in Example 5, except that LiNi 0.6 Co 0.2 Mn 0.2 O2 replaced by LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0183] Comparative Example 1
[0184] The method is the same as that in Example 1, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) was adjusted to 94.5:0:3:1.5.
[0185] Comparative Example 2
[0186] The method is the same as that in Example 1, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 49.7:44.8:3:1.5.
[0187] Comparative Example 3
[0188] The method is the same as that in Example 5, except that lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2)、LiMn 0.75 Fe 0.25 The weight ratio of PO4, lithium squarate, conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) is adjusted to 70:24.5:7.7:3:1.5.
[0189] Pole piece porosity test
[0190] 1. Porosity test of positive electrode sheet:
[0191] The test was conducted on the fully automatic true density tester AccuPycⅡ1340 according to GB / T 24586-2009. Specifically, the positive and negative electrodes were cut into 14 mm diameter discs, placed in a sample cup, placed in the true density tester, and the closed test system was introduced with helium according to the program. The pressure of the gas in the sample chamber and the expansion chamber was detected, and the real volume was calculated according to Bohr's law (PV=nRT), thereby obtaining the porosity of the sample to be tested. The test results are shown in Table 1 below.
[0192] 2. Negative electrode porosity test:
[0193] The test method is the same as that of the positive electrode plate porosity. The test results are shown in Table 1 below.
[0194] Lithium-ion battery performance test
[0195] Battery capacity retention test:
[0196] Taking Example 1 as an example, the battery capacity retention rate test process is as follows: at 25°C, charge the battery corresponding to Example 1 at a constant current of 1 / 3C to the termination voltage, then charge it at a constant voltage to 0.05C, leave it for 5 minutes, and then discharge it at 1 / 3C to the discharge cut-off voltage. The obtained capacity is recorded as the initial capacity C0. Repeat the above steps for the same battery mentioned above, and simultaneously record the discharge capacity Cn of the battery after the nth cycle. Then the battery capacity retention rate Pn after each cycle is Cn / C0*100%. During this test process, the first cycle corresponds to n=1, the second cycle corresponds to n=2, and... the 1500th cycle corresponds to n=1500. The battery capacity retention rate data corresponding to Example 1 in Table 1 are the data measured after 1500 cycles under the above test conditions. The test process of other embodiments and comparative examples is the same as above.
[0197] Table 1
[0198]
[0199]
[0200]
[0201] It can be seen from Examples 1-4 that as LiMn 0.75 Fe 0.25 As the proportion of PO4 increases, the lattice contraction of the positive electrode sheet matches the expansion of silicon, and the cycle capacity retention rate is improved; continue to increase LiMn 0.75 Fe 0.25 The proportion of PO4 is too high, and the cycle begins to deteriorate due to its fast cycle decay under the voltage of the ternary system. Therefore, it is necessary to control the LiMn 0.75 Fe 0.25The amount of PO4 added is within a reasonable range to avoid lithium plating at the negative electrode and improve the battery's cycle capacity retention rate.
[0202] It can be seen from Example 1 and Comparative Examples 1-2 that Comparative Example 1 does not add LiMn 0.75 Fe 0.25 PO4, Comparative Example 2 Adding excess LiMn 0.75 Fe 0.25 PO4, the capacity retention rates of Comparative Examples 1-2 are significantly lower than those of Example 1. 0.75 Fe 0.25 The amount of PO4 added has a significant effect on the cycle performance of the battery.
[0203] It can be seen from Examples 5-10 and Comparative Example 3 that as the amount of lithium squarate added increases, the porosity of the electrode increases, the amount of electrolyte that can be accommodated increases, and the cycle is improved, but excessive porosity causes the electrolyte demand to exceed the actual amount, and the cycle deteriorates.
[0204] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A pole piece structure, characterized in that: include: A positive electrode sheet, the positive electrode sheet comprising a positive electrode active material, the positive electrode active material comprising a ternary positive electrode material and LiMn a Fe b A mixture of PO4, where 0≤a<1,0 <b≤1,a+b=1; as well as A negative electrode plate, wherein the negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material comprises the carbon-based material and the silicon-based material.
2. The pole piece structure according to claim 1, characterized in that: LiMn a Fe b The mass ratio of PO4 to the ternary positive electrode material is 0.01-0.
7.
3. The pole piece structure according to claim 1, characterized in that: The mass ratio of the silicon-based material to the carbon-based material is 0.01-0.
1.
4. The pole piece structure according to any one of claims 1 to 3, characterized in that: The mass ratio of the silicon-based material to the carbon-based material is defined as P, and LiMn a Fe b The mass ratio of PO4 to the ternary positive electrode material is Q, and R=Q / P satisfies: 0.5≤R≤15.
5. The pole piece structure according to claim 1, characterized in that: The positive electrode sheet is formed of a positive electrode slurry, which includes the positive electrode active material and further includes a gas generating additive.
6. The pole piece structure according to claim 5, characterized in that: The gas generating additive includes one or both of a non-lithium-supplementing gas generating additive and a lithium-supplementing gas generating additive. The non-lithium-supplementing gas generating additive includes one or more of ammonium bicarbonate, sodium bicarbonate, and ammonium carbonate. The lithium-supplementing gas generating additive includes one or more of lithium nitride, lithium oxide, lithium peroxide, lithium squarate, and lithium oxalate.
7. The pole piece structure according to claim 6, characterized in that: The mass ratio of the gas generating additive to the ternary positive electrode material is 0.001-0.
1.
8. The pole piece structure according to claim 7, characterized in that: The mass ratio of the gas generating additive to the ternary positive electrode material is 0.001-0.1, and the mass ratio of the silicon-based material to the carbon-based material is 0.01-0.
1.
9. The electrode structure according to claim 7, wherein the mass ratio of the silicon-based material to the carbon-based material is P, and the mass ratio of the gas generating additive to the ternary positive electrode material is defined as V, then W=V / P satisfies: 0.1≤W≤2.
10. The pole piece structure according to claim 1, characterized in that: The porosity of the positive electrode sheet is 15%-30%.
11. The pole piece structure according to claim 1, characterized in that: The porosity of the negative electrode plate is 20%-40%.
12. The pole piece structure according to any one of claims 1 to 4, characterized in that: The ternary positive electrode material includes LiNi x Co y Mn z O2, where 0 <x<1,0<y<1,0<z<1,x+y+z=1。 13. A secondary battery comprising the pole piece structure according to any one of claims 1 to 12.
14. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 13.